U-Th dating, taphonomy, and taxonomy of shell middens at Klasies River main site indicate stable and systematic coastal exploitation by MIS 5c-d - Wurz, Sarah; Pickering, Robyn; Mentzer, Susan M. (Frontiers in Earth Science, 2022)
The archaeological record, particularly of shellfish, from the Klasies River main site (KRM) is important in understanding the fluctuating nature of coastal occupational patterns and changing coastal ecologies. In this paper, we provide new uranium–thorium (U-Th) dates for one of the earlier phases of coastal exploitation at KRM, and the microstratigraphic analyses generate novel information about the taphonomy of shell-bearing deposits from the Later Stone Age (LSA) to the MSA I period that, in turn, provide a broader context for middening at the site. A wide range of syndepositional taphonomic processes related to human activities and post-depositional effects include burning, fragmentation and compaction, chemical alteration, and cementation. Despite such issues influencing recovery, shellfish data are informative and are presented from three layers of the Witness Baulk: Shell Midden One (SMONE), Black Occupational Soils (BOS), and Silty Black Soils (SBLS). These coarse shell midden deposits exhibit visible decalcification coupled with cementation with secondary carbonate formation in association with conditions of high moisture and soft sedimentation deformation of the underlying sediments of SBLS. This stratigraphy section is chronologically anchored for the first time using U-Th dating of speleothems associated with a hiatus after the deposition of BOS. The three ages, 110,060 ± 1,100, 109,800 ± 970, and 106,000 ± 2,100 years, place the BOS layer as the base of the SASL sub-member at over 110 ka, making the underlying middens from the LBS member even older. The zooarchaeological analyses of the three layers indicate coastal ecological changes from more sheltered conditions prior to the hiatus, with the exploitation of alikreukel and brown mussels predominating. Before 110 ka, in BOS and SBLS, more exposed coastal conditions occurred, and the diversity of exploited shellfish increased. SMONE and BOS are associated with MSA II/Mossel Bay lower lithic technology and SBLS with MSA I technology, indicating asynchronous coastal ecological and technological changes. The MIS 5c-d evidence for early coastal occupation at KRM provides details on the period during which coastal occupation became stable and systematic on the South African coast and puts the KRM amongst the handful of sites with shell-bearing deposits, occurring prior to 110 ka in South Africa.